“EVERY MAN HAS HIS DAY IN COURT”: PROVERBS, SAYINGS, AND PROVERBIAL EXPRESSIONS OF THURGOOD MARSHALL - Summerville, Raymond M. (Proverbium - Yearbook, 2025)
This essay explores some of the proverbs, sayings, and proverbial expressions used by Thurgood Marshall, the first African-American Supreme Court Justice (1967). It argues that Marshall’s proverbial language use conveys several aspects of his worldview including his philosophy concerning race, class, and social justice in American society. The essay also aims to illustrate ways that Marshall’s multifaceted proverbial language use demonstrates the sound knowledge he possessed in the area of legal studies and the exceptional talent he possessed in the areas of rhetoric and deliberation. Furthermore, the essay reveals some of the ways Marshall used proverbial language to connect with other people as he incorporated various proverbs and phrases into his speech which would help make legal language more accessible to common folk (especially the people he would represent as an NAACP and LDF attorney) while also allowing him to capitalize on opportune rhetorical moments in the courtroom. The essay utilizes several Marshall biographies, interviews, and legal documents as source material. It also incorporates the scholarship of other paremiologists such as Wolfgang Mieder, Anna T. Litovkina, Sanda Eretescu Golopentia, Harvey Sack, and others to address issues concerning: categorization, definition, origin, meaning, interpretation, and context.